(untitled) (Economics and region, 2019)
The article investigates the dynamics of merger and acquisition of Ukrainian companies abroad. The main consequences of merger and acquisitions for the Ukrainian companies are highlighted. It is proposed measures to improve content and distribution of M&A of Ukrainian companies. The result of the research is that the main problems are today inhibit the process of attracting M&A, are: political and legislative instability; the problem of providing reliable guarantees protection against changes in Ukrainian legislation; significant tax and administrative pressure; high level of corruption and bureaucracy; high inflation in the country and complicated registration process; licensing and customs procedures. The main ways solving problems of mergers and acquisitions should be: improving the investment climate by improving the general and special legislation that regulates the relationship in the investment, respectively to European norms; execution of investment projects on the principle of "single window"; introduction of the economic mechanism of insurance of foreign investment risks; provide government guarantees to investors and consolidate them at the legislative level. Further research should be conducted to form an effective investment, mergers policy that would contribute to attracting foreign investment in the country for extending Ukrainian market.